Transcriptional regulatory mechanisms involved in CYP46A1 up-regulation by histone deacetylase inhibitors:from chromatin structure to transcription factors - Nunes, MJ (2013)
Tese de doutoramento, Farmácia (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Farmácia, 2012